A new Polychrysia (Lepidoptera, Noctuidae, Plusiinae) species from China - Saldaitis, Aidas; Benedek, Balázs (Zootaxa, 2015)
The genus Polychrysia is comprised of seven species separated into three species groups. Six of the seven species are distributed in the Palaearctic region and one of these six species has a Holarctic distribution. The genus has been discussed in detail in monographs by Goater et al. (2003) and Ronkay et al. (2008). A new species of Polychrysia was discovered during an expedition studying the nocturnal fauna of China’s Sichuan Province in August, 2014 and is described here.